Frosted windows and compartmentalized intimacies: Forging relationships in a Bolivian restaurant in Madrid. Issue 3 (1st October 2016) - Sammells, Clare A.
ABSTRACT: Bolivian restaurants in Madrid, like other Spanish restaurants, obscure clients from public view, complicating the idea of restaurants as public space. These are locations of "compartmentalized intimacy" that both blur and maintain divisions between restaurant staff, customers, family members, and friends. The deliberate structuring of space to create the semi-public nature of the restaurant is part of a larger process of "culinary translation" between the multiple audiences that interact in this space. Such translations involve not only the preparation and modification of dishes but also the structure of spaces where this food and drink are consumed. In other words, how space is organized within the restaurant is as much a part of the interactions between staff and customers as the food and drink they serve. All these translations, while always context-specific and incomplete, actively forge "compartmentalized intimacies" between the Bolivian, Spanish, and Chinese clients and the Bolivian owner and staff who eat there. These intimacies are not always proportional to how much money changes hands, even though they are mediated by their commercial nature.